Sound and light [videorecording (DVD)] - Mazzarella, Tony (Start smart. Science I need to know., 2013)
Volume one: Sound, helps viewers learn the principles of sound, the range of human hearing and significant terms, as they discover the science behind everyday sounds. Volume Two: Light, features real world demonstrations and colorful graphics to teach the different properties of light, pertinent definitions and how light travels. Learn how different mediums can affect light, resulting in reflection, refraction and absorption.